Exploring the roles of snoRNA-induced ribosome heterogeneity in equine osteoarthritis - Chabronova, Alzbeta; Walters, Marie; Regårdh, Sara; Jacobsen, Stine; Bundgaard, Louise; Anderson, James R.; Peffers, Mandy J. (Frontiers in Veterinary Science, 2025)
IntroductionOsteoarthritis (OA) is a degenerative joint disease that greatly contributes to equine morbidity and poor welfare. Changes in cellular protein expression programs fuel the development and progression of OA. Small nucleolar RNAs (snoRNAs) are emerging as important regulators of OA (patho)biology. SnoRNAs are short non-coding RNAs that guide post-transcriptional modifications (PTMs) of ribosomal RNA (rRNA) nucleotides, which impact ribosome function and thus cellular protein expression programs. There is only very limited data on snoRNAs in equine OA.MethodsIn this study, we induced OA in horses (n = 9) using a well-established equine carpal osteochondral fragment model of OA. We collected synovial fluid (SF) before (Day 0) and after OA-inducing surgery (Day 28, Day 70). Using small RNA sequencing, we then measured snoRNA levels in SF.ResultsWe identified 229 snoRNAs across all samples of which 30 snoRNAs were significantly differentially expressed (DE) in Day 28 vs. Day 0 comparison, 22 snoRNAs in Day 70 vs. Day 0, and finally, 23 snoRNAs in Day 70 vs. Day 28. On Day 28, the majority of DE snoRNAs were upregulated when compared to Day 0. In contrast, the majority of DE snoRNAs on Day 70 were downregulated when compared to Day 0 and Day 28. Altogether, 44 snoRNAs were DE across different comparisons, the majority of which were canonical snoRNAs. We then mapped all the predicted PTMs guided by the DE snoRNAs within a 3D ribosome.DiscussionSeveral of these PTMs were located within functionally important ribosomal regions. This included helices H89–H91 of peptidyl transferase center, helices H37–H39 of A-site finger and B1a ribosomal bridge, helices H70–H71, 5.8S-28S junction, and lastly, helices h14 and H95 of GTPase-associated center. Altogether, our novel data show that snoRNAs are regulated in equine OA, highlighting their potential as early molecular biomarkers and therapeutic targets. Targeting snoRNA to modulate protein synthesis in OA joints could ultimately improve outcomes for OA-affected horses.